Pengaruh Kinerja dan Kualitas Pelayanan terhadap Kepuasan Pelanggan Klinik AA+ Dental Care Sakra Lombok Timur - Talidobel, Susilo; Jati, L. Jatmiko; Assa’ady, M. Chothibul Umam; Wardi, Putri Amalia (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Performance and quality of service are closely related to customer satisfaction. The progress of a company is influenced by the company's ability to serve its customers. The services provided by the company must pay attention to the standard quality given to customers and must even exceed what is expected by customers so that customer satisfaction can be easily obtained by the company, because it can make customers continue to use the company's services. This study aims to determine the effect of performance and quality of service on customer satisfaction at the AA + Dental Care Sakra Clinic. The method used in this study is a quantitative method. The sample of this study was 60 respondents who were determined by Systematic Random Sampling. The results of this study indicate that the effect of service quality has a strong relationship with customer satisfaction. This can be shown from the results of the correlation coefficient test, the results of the determination coefficient test obtained a significant effect so that it means that customer satisfaction can be influenced by service performance; although customer satisfaction is still influenced by other factors that are not examined in this study.